2016
DOI: 10.1038/nrneurol.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Managing the complexity of multiple sclerosis

Abstract: The application of imaging biomarkers has provided new insights into the mechanisms of damage in multiple sclerosis (MS) and the risk of MS development and progression. The goal of eliminating all disease activity requires a timely escalation of treatment. This increasing complexity is compounded by the need to treat comorbidities.Multiple sclerosis (MS) is an increasingly complex disease in terms of its pathogenesis, comorbidities, prognosis and treatment, and successful patient management requires knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…More recently, studies have shown loss of RGC axons occurs in multiple sclerosis patients even in the absence of acute optic neuritis, and correlates with length of disease 45 46 , suggesting a progressive neurodegenerative process that is not prevented by current multiple sclerosis medications. Indeed, current therapies modulate immune responses and reduce disease relapses 47 48 , but show limited potential to prevent neurodegeneration and neurologic dysfunction. For optic neuritis specifically, there is no treatment that alters visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, studies have shown loss of RGC axons occurs in multiple sclerosis patients even in the absence of acute optic neuritis, and correlates with length of disease 45 46 , suggesting a progressive neurodegenerative process that is not prevented by current multiple sclerosis medications. Indeed, current therapies modulate immune responses and reduce disease relapses 47 48 , but show limited potential to prevent neurodegeneration and neurologic dysfunction. For optic neuritis specifically, there is no treatment that alters visual outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis, currently based on clinical parameters, the number, size and location of lesions detected by MRI and spinal fluid diagnostics, is often delayed due to heterogeneous symptoms and long recovery phases at the beginning of the disease 2 , thus preventing timely therapy initiation 3 , and other neurologic diseases may mimic the symptoms in early phases 4 – 6 . The search for biomarkers to improve the diagnosis of MS is an active research topic 7 . Approaches include positron emission tomography addressing neuro-inflammation and astrocyte markers 8 , genetic, immune-inflammatory, and oxidative stress markers 9 , Vitamin D binding protein isoforms and apolipoprotein E in cerebrospinal fluid 10 , and plasma micro RNAs 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…In the early stages, MS often appears in a relapsing-remitting pattern, but in the later stage the disease develops into a secondary progressive phase without remission [2]. Currently, no effective treatment is available for progressive MS [3]. In the development of MS, the immune response plays a key role in the processes of demyelination and nerve injury, which jointly promote disease progression [4,5].…”
Section: Introductionmentioning
confidence: 99%